Effect of intermolecular interaction of the charge-transfer complex between molecular "tweezers" and C60/C70 on second-order nonlinear optical properties. Issue 12 (13th March 2023) - Wang, Li; Liu, Yan-Li; Li, Quan-Jiang; He, Di; Chen, Sheng-Hui; Wang, Mei-Shan
Abstract : Through increasing the volume of fullerene and embedding alkali metal ions, we could enhance intermolecular interactions and intermolecular CT significantly, thereby improving the second-order NLO properties of CT complexes. Abstract : To enhance understanding of the correlation between the intermolecular interaction and second-order nonlinear optical (NLO) properties, we studied a "molecular tweezer" with two corannulene substituents linked by a tetrahydro[5]helicene imide, which enabled highly sensitive and selective complexation of C60 /C70 through convex–concave π–π interactions. The geometric structure, molecular orbitals, intermolecular interactions, electron absorption spectra and second-order NLO properties of the charge-transfer (CT) complexes formed by molecular tweezers and C60 /C70 were studied by density functional theory. Larger fullerenes helped to increase the intermolecular interaction and CT, thereby increasing the first hyperpolarizabilities of CT complexes. Embedding of lithium ions helped to enhance the electron-absorption ability of fullerenes, thereby increasing the intermolecular interaction and intermolecular CT and, thus, enhancing their first hyperpolarizability significantly. Our data indicated that, through structure adjustment (including increasing the volume of fullerene and embedding alkali metal ions), we could enhance intermolecular interactions and improve intermolecular CT significantly. These actions could improve the second-order NLO properties of CT complexes.